The Effect of Workload and Work Environment on Medication Error through Adherence to Medication Procedures in Hospitals: A Literature Review - Sri Fatmiyati; Burhanuddin Ichsan; Muzakar Isa (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
This article aims to develop a proposition about the factors that influence medication errors in hospitals. This study selected articles using the keyword "medication error" for articles in the range years of 2020 to 2025. We have conducted an initial selection process to find out which articles are suitable for medication errors. We also selected and reviewed 17 articles that discussed the relationship between the effects of workload, work environment and adherence to medication errors. Based on the results of the theoretical study, workload and work environment affect medication error and adherence to medication administration procedures as intervening variables. Workload and work environment affect medication error. According to the theory of planned behavior, a person behaves because they are driven by a certain stimulus, then the work environment is not conducive and the high workload received by employees, will decrease performance and increase the risk of errors. Therefore, it is important for managers to create a conducive work environment, manage a balanced workload and according to capacity, increase employee compliance with SOPs through training, supervision, and internal audits.